Health threats to Polish firefighters during vehicle fires – analysis of fire and rescue operations in Poland in 2017–2022. - Dudziński, Łukasz; Bihałowicz, Jan Stefan; Weiner, Marcin; Kasperczyk, Rafał; Kubiak, Tomasz (Work, 2025)
Background: Firefighters while extinguishing fires, are exposed to air pollution resulting from combustion processes, especially dangerous when originating from the combustion of plastics. Air pollution during a fire results from the release of gases, vapors, smokes, and dusts of varying composition and toxicity levels into the atmosphere. Objective: To analyse and estimate the health hazards to firefighters resulting from exposure to harmful chemical compounds generated during vehicle fires in Poland between 2017 and 2022. Methods: Data from the Decision Support System of the State Fire Service (DSS-SFS), provided by the Operational Planning Office, were used. Events from the period 1st January 2017—31st December 2022 were analysed. Quantitative data were described using the mean (Mean) and standard deviation (SD). Correlations and differences at the significance level of p < 0.05 were considered statistically significant. The analysis is anonymous for both the victims and the officers involved in the described fire and rescue operations. Results: According to the DSS-SFS system records, firefighters carried out n = 55,422 (min 8441, max 9847, mean 9237, SD 494.2) fire interventions (F), in the category of object: motor vehicles, during 2017–2022. The maximum firefighting operation times were observed for trucks, which may result from the purpose of these vehicles (carrying loads), the necessity of firefighting operations in the cargo space and the transported materials. Conclusion: Attention should be paid to the various possibilities of exposure to fire substances, not only directly at the source of combustion but also in the fire engine, on protective clothing, firefighting equipment, which can cause secondary exposures long after the firefighting operation has ended, and the correct decontamination process..